(untitled) - Linden, Allen M. (Markham, Ont., 2006)
Derived from the renowned multi-volume International Encyclopaedia of Laws, this book provides ready access to how the legal dimension of prevention against harm and loss allocation is treated in Canada. This traditional branch of law not only tackles questions which concern every lawyer, whatever his legal expertise, but also concerns each person’s most fundamental rights on a worldwide scale.
Keywords: Torts,Vi phạm pháp luật; Canada,Canada